Simulation of a common source multilevel inverter as frequency variator for induction motors - Pabón-Fernández, Luis David; Díaz-Rodríguez, Jorge Luis; Pardo-García, Aldo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper describes the simulation of a three-phase multilevel common source converter of 15-line levels, as variable frequency drive for fed induction motors. The variable frequency drive is optimized in the first 50 harmonic responses; the optimization algorithm was developed in Matlab. The simulation results validate the benefits of this kind of fed induction motor with regard of the power quality in both: voltage and electrical current behaviour.